IDEOLOGY IN INDONESIAN TRANSLATION OF MELILEA PRODUCT PACKAGING - Nur Laili Yusuf (PPPM STIT MIFTAHUL MIDAD, 2022)
This study aims to examine the ideology employed by translators in resolving the translation problems of Melilea product packaging translation texts from English to Indonesian. This study seeks to determine the ideology employed by the translator in the process of text translation. The data is translation text that appears on Melilea product packaging as a word, phrase, clause, or sentence. The analysis reveals that a translator employed two ideologies, foreignization and domestication, with foreignization comprising about 70 percent and domestication about 30 percent of the total. In addition, the translator discovered the advantages and disadvantages of utilizing both ideologies. In this study, the translator utilized foreignization more frequently than domestication.